A contemporary survey on free space optical communication: Potentials, technical challenges, recent advances and research direction. (April 2022) - Jahid, Abu; Alsharif, Mohammed H.; Hall, Trevor J.
Abstract: Due to the unprecedented growth of high speed multimedia services and diversified applications initiated from the massive connectivity of IoT devices, 5G and beyond 5G (B5G) cellular communications, the existing electromagnetic spectrum under RF ranges is incapable to tackle the enormous future data rate demands. Free space optical (FSO) communication systems covering an ultra-wide range of unlicensed spectrum have emerged as a promising solution to mitigate conventional RF spectrum scarcity ranging of communication distances from nm to several kilometers. The implication of hybrid FSO, radio over FSO (RoFSO), MIMO FSO systems support ultra high speed 5G/B5G demand by eliminating the limitations of individual technology. FSO offers a broad range of applications both in outdoor and indoor services, for instance, wireless video surveillance, data centers, terrestrial transmission, LAN connectivity, mobile cellular networks, last mile solution, space communications, radio astronomy, remote sensing, and so on. Despite the potential benefits of FSO technology, its link reliability deteriorates due to atmospheric turbulence, cloud induced fading, some other environmental factors such as fog, aerosol, temperature variations, storms, heavy rain, pointing error, and scintillation. This survey presents the overview of several key technologies, significance, demonstration, recent development, and implications of state-of-the-art criteria in terms of spectrum reuse, classification, architecture, physical layer security, and future applications for understanding FSO system among different appealing optical wireless technologies. In addition, the adaptive modulation, channel modeling schemes, relay-aided transmission, cooperative diversity, potential challenges, numerous mitigation techniques, and opportunities in the near future are also outlined to realize the successful deployment of FSO systems. Highlights: Outline the scope of hybrid FSO, multiuser FSO, MIMO-FSO, coherent FSO. Survey on FSO channel modeling, diversity technique, relay transmission, link budget. Demonstrate the potential key features of FSO in 5G/B5G, IoT/IoE, space domain. Provide extensive comparison between FSO and other OWC technologies.